The Influence Of Work Skills, Work Spirit, Work Ability And Workload On The Quality Of Public Services In Regional Development Planning Agency Nature Fence City - Rafles Lasido; Hardiyansyah Hardiyansyah; Nisma Aprini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine and analyze the effect of work skills, morale, work ability, and workload on the quality of public services at the Regional Development Planning Board of Pagar Alam City. This study uses quantitative research methods with respondents, namely employees of the Regional Development Planning Board of Pagar Alam City, totaling 41 respondents. Tests in this study used multiple linear regression analysis with the tools of the SPSS (Special Package and Service Solution) version 26 program. The results of the study show that work skills, work enthusiasm, work ability, and workload have proven to have a significant effect on the quality of public services at the Regional Development Planning Agency of Pagar Alam City, both partially and simultaneously.